2018
DOI: 10.1002/prca.201800065
|View full text |Cite
|
Sign up to set email alerts
|

Integration of “Omics” Strategies for Biomarkers Discovery and for the Elucidation of Molecular Mechanisms Underlying Brugada Syndrome

Abstract: This study provides the basis to shed light on the specific molecular fingerprints underlying BrS development and to gain further insights on the pathogenesis of this life-threatening cardiac disease.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 77 publications
0
8
0
Order By: Relevance
“…Scumaci et al . 33 studied 179 miRNAs in 13 Brugada patients and 10 control individuals but did not find a molecular signature that was associated with adverse cardiac events. The sample size and number of screened miRNA molecules in their study may account for these differences.…”
Section: Discussionmentioning
confidence: 99%
“…Scumaci et al . 33 studied 179 miRNAs in 13 Brugada patients and 10 control individuals but did not find a molecular signature that was associated with adverse cardiac events. The sample size and number of screened miRNA molecules in their study may account for these differences.…”
Section: Discussionmentioning
confidence: 99%
“…Indeed, genes associated with BrS, such as SCN5A , have been shown to be expressed throughout the body and could contribute to the occurrence of overlapping pathologies, although solid evidence of a multi-organ or systemic disease is still lacking [ 26 ]. Moreover, observations of altered plasma proteins in BrS patients were not conclusive [ 24 , 25 ], as they could simply reflect cardiac dysfunction [ 27 ]. In this study, we provide decisive evidence that BrS also affects extracardiac tissues, as we found significant alterations in gene expression and protein sialylation in PBMCs of affected patients.…”
Section: Discussionmentioning
confidence: 99%
“…Surprisingly, the involvement of sialylation in BrS remains unknown. Although alterations in plasma proteins have been reported in BrS patients [ 24 , 25 ], changes in the protein sialylation machinery or other PTMs have not been investigated.…”
Section: Introductionmentioning
confidence: 99%
“…The importance of non-coding RNAs in the context of Brugada syndrome has been recently explored using an integrative omics approach [388]. These authors identified several microRNAs that are distinctly upregulated in BrS, such as miR-92a-3p and miR-320b, or down-regulated such as miR-425-5p and established their plausible links as molecular determinants of Brugada syndrome, yet functional evidence is missing.…”
Section: Brugada Syndromementioning
confidence: 99%